Proteomic signatures of myeloid derived suppressor cells from liver and lung metastases reveal functional divergence and potential therapeutic targets - DaSilva, Nicholas A.; Barlock, Benjamin J.; Guha, Prajna; Ghosh, Chandra C.; Trebino, Catherine E.; Camberg, Jodi L.; Katz, Steven C.; Rowley, David C. (Cell death discovery, 2021)
Myeloid-derived suppressor cells (MDSCs) promote immunosuppressive activities in the tumor microenvironment (TME), resulting in increased tumor burden and diminishing the anti-tumor response of immunotherapies. While primary and metastatic tumors are typically the focal points of therapeutic development, the immune cells of the TME are differentially programmed by the tissue of the metastatic site. In particular, MDSCs are programmed uniquely within different organs in the context of tumor progression. Given that MDSC plasticity is shaped by the surrounding environment, the proteomes of MDSCs from different metastatic sites are hypothesized to be unique. A bottom-up proteomics approach using sequential window acquisition of all theoretical mass spectra (SWATH-MS) was used to quantify the proteome of CD11b + cells derived from murine liver metastases (LM) and lung metastases (LuM). A comparative proteomics workflow was employed to compare MDSC proteins from LuM (LuM-MDSC) and LM (LM-MDSC) while also elucidating common signaling pathways, protein function, and possible drug-protein interactions. SWATH-MS identified 2516 proteins from 200 µg of sample. Of the 2516 proteins, 2367 have matching transcriptomic data. Upregulated proteins from lung and liver-derived murine CD11b + cells with matching mRNA transcriptomic data were categorized based on target knowledge and level of drug development. Comparative proteomic analysis demonstrates that liver and lung tumor-derived MDSCs have distinct proteomes that may be subject to pharmacologic manipulation.